New series 17, no. 2, Winter 2009 - Baird, Catherine; Plessl, Anne (My University, 2009)
This issue of McMaster Library News includes the following articles:
McMaster Libraries now among top 100 research libraries in North America
Renovating the Thode Library of Science & Engineering
A redesigned library website
Portico
Peace and War in the 20th Century now live
Historical Perspectives on Canadian Publishing
Web 2.0 Toolbox
Library takes on new role as publisher
Reorganization and new staff
New spaces and services to make busy lives easier
Recent notable acquisitions
Recent notable gifts